Ratio Legis Unsur Tanpa Hak Dalam Perundangan Tentang Penggunaan Senjata Tajam Di Indonesia - Fendi Anto; Febriana Nur Widyaningsih; Suratman Suratman; Moh. Muhibbin (Nuansa Akademik: Jurnal Pembangunan Masyarakat, 2022)
Law appears in accordance with the political and social configuration of a certain period. This fact indicates that the law continues to require renewal. One of the proofs that the law cannot reach people's lives which continues to develop is the emergence of Emergency Law no. 12 of 1951. The emergency law emerged as a renewal of the Republic of Indonesia Law No. 8 of 1948, and changed the Ordonnantie Tijdelijke Bijzondere Strafbepalingen (sbtl. 1948 No. 17). At certain times the emergency law was the right solution, but now the law that has not been updated can cause problems. One of the problems that arise is the ambiguity of the "without rights" element in the use of sharp weapons. The law does not specify which party has the right or the right to not use sharp weapons. In order for the law to continue to be used, a ratio legis is needed. This study aims to examine (1) the ratio of the elements of "without rights" in Article 2 of Law no. 12 of 1951, and (2) the configuration of the concept of Article 2 of Law no. 12 Year 1951 which is ideal in the future. This research is juridical-normative research with a statutory approach. The technique of analyzing legal materials is done by qualitative descriptive. The results of this study include, (1) the phrase "without rights" needs to be specified so as not to cause multiple interpretations, and (2) Law no. 12 of 1951 is no longer relevant to use.